2001
DOI: 10.1002/1097-0231(20010130)15:2<135::aid-rcm204>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

High-performance liquid chromatography/electrospray tandem mass spectrometry of polycyclic aromatic hydrocarbons

Abstract: Selected ion chromatograms of the polyaromatic hydrocarbons anthracene, pyrene and 1,2‐benzanthracene were recorded using high‐performance liquid chromatography coupled to electropspray ionisation mass spectrometry after derivatisation with tropylium cation to produce positive ions. LC/ESI‐MS/MS was then performed at five different collision energies (25–125eV) using m/z 178, 202 and 228 as precursor ions. Best fragment patterns were obtained in product ion mode at 100 eV. Copyright © 2001 John Wiley & Sons, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
1
17
1
Order By: Relevance
“…in both APCI and ESI mode. Consequently, the charge transfer dominated the process of ion formation rather than the proton transfer in the APCI source, which is consistent with the report of Perez and Barcelo;8 the charge transfer was also dominant for the ion formation of PAHs than that of the formation of the PAH‐tropylium complex in the ESI source, which is in agreement with the finding of Airiau et al 13…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…in both APCI and ESI mode. Consequently, the charge transfer dominated the process of ion formation rather than the proton transfer in the APCI source, which is consistent with the report of Perez and Barcelo;8 the charge transfer was also dominant for the ion formation of PAHs than that of the formation of the PAH‐tropylium complex in the ESI source, which is in agreement with the finding of Airiau et al 13…”
Section: Resultssupporting
confidence: 92%
“…Applications of ESI on non‐polar chemicals such as PAHs are limited, because they usually require chemical derivatizations. Tropylium (TR + )12, 13 or Ag + (as silver nitrate)14 cations have been used as electron acceptors and have been added post‐column to the eluent to yield cationic adducts of PAHs. Although the addition of silver salts may provide a better sensitivity than that of tropylium cations in LC/ESI‐MS and the detection limits, ≈0.02–0.6 ng of on‐column injection, are similar to those of GC/MS, silver ions may deposit in the instrument making more frequent maintenance necessary 15…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neither method can ionize analytes without easily ionizable functional groups, such as saturated and unsaturated hydrocarbons, in the presence of basic or acidic analytes [7,8]. In order to enable the analysis of polycyclic aromatic analytes, some investigators have derivatized them prior to ESI/mass spectrometry [9]. Other methods used to facilitate the analysis of polyaromatic hydrocarbons include using silver cationization or adding CHCl 3 into the ESI solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Using this procedure, the PAHs and 1-nitropyrene were simultaneously determined by LC/ESI/MS. Furthermore, the cationization of PAHs by post-column addition of tropylium was applied to LC/ESI/MS/MS [33]. Takino et al (2001) [34] have reported the use of silver ions, instead of electron-transfer reagents or tropylium ions, as a post-column reagent for the formation of PAH complexes.…”
Section: Discussion 21 Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%